Two new species of ant-loving beetles (Coleoptera: Staphylinidae: Pselaphinae) from Jiulong National Wetland Park, China - Zhang, Yong-Qin; Wei, Guo-Hao; Yin, Zi-Wei (Zootaxa, 2024)
Continued collecting efforts at the Jiulong National Wetland Park, Zhejiang, East China revealed two additional species of the ant-loving beetle subfamily Pselaphinae (Coleoptera: Staphylinidae): Trisiniotus jiulong sp. nov. and Arthromelodes lianghongbini sp. nov. Both new species are diagnosed, described, and their important characters are illustrated.